Biodegradable inorganic-organic hybrids of methacrylate star polymers for bone regeneration - Chung,JJ; Fujita,Y; Li,S; Stevens,M; Kasuga,T; Georgiou,T; Jones,JR (Acta Biomaterialia, 2017)
Hybrids that are molecular scale co-networks of organic and inorganic components are promising biomaterials, improving the brittleness of bioactive glass and the strength of polymers. Methacrylate polymers have high potential as the organic source for hybrids since they can be produced, through controlled polymerization, with sophisticated polymer architectures that can bond to silicate networks. Previous studies showed the mechanical properties of hybrids can be modified by polymer architecture and molar mass (MM). However, biodegradability is critical if hybrids are to be used as tissue engineering scaffolds, since the templates must be remodelled by host tissue. Degradation by-products have to either completely biodegrade or be excreted by the kidneys. Enzyme, or bio-degradation is preferred to hydrolysis by water uptake as it is expected to give a more controlled degradation rate. Here, branched and star shaped poly(methyl methacrylate-co-3-(trimethoxysilyl)propyl methacrylate) (poly(MMA-co-TMSPMA)) were synthesized with disulphide based dimethacrylate (DSDMA) as a biodegradable branching agent. Biodegradability was confirmed by exposing the copolymers to glutathione, a tripeptide which is known to cleave disulphide bonds. Cleaved parts of the star polymer from the hybrid system were detected after 2 weeks of immersion in glutathione solution, and MM was under threshold of kidney filtration. The presence of the branching agent did not reduce the mechanical properties of the hybrids and bone progenitor cells attached on the hybrids in vitro. Incorporation of the DSDMA branching agent has opened more possibilities to design biodegradable methacrylate polymer based hybrids for regenerative medicine.Statement of significanceBioactive glasses can regenerate bone but are brittle. Hybrids can overcome this problem as intimate interactions between glass and polymer creates synergetic properties. Implants have previously been made with synthetic polymers that degrade by